Technology for obtaining electric energy from forestry residues at the Macurijes Agroforestry Enterprise (EAF), Macurijes, Cuba - Castillo Edua, Bertha Rita; Ciencias Forestales. Facultad de Ciencias Forestales y Agropecuarias. Universidad de Pinar del Río, CUBA (2023)
The objective of this investigation was to evaluate the technology proposal for a process of generating electrical energy from the residues of the forest exploitation of the Macurijes Agroforestry Company. For which a proposal for steam boiler technology is analyzed based on the potential of standing forest biomass and forest residues, as well as an analysis of the feasibility of the technology investment project. As a result, 6 MWh of generation is obtained from the turbine coupled to the electric generator based on 62,000 tons per year, 1,666 t/day, which represents around 7/t/ hours with a boiler that produces steam at 25 atm or bar at 460 degrees Celsius in 7,000 hours per year as a result of periodic maintenance stops. The boiler to be used must have water tubes since they work at high pressure, are easier to clean, evacuate ashes, combustion products and are safer in their operation and that average PCS of 2,7 Kcal/kg with a humidity of 40 % as a result of the combination of a heterogeneous biomass composed of several forest species and the previous treatment given to it.